Sistema de gestión de calidad según la ISO 9001:2015 para el Gobierno Autónomo Descentralizado del Cantón San Miguel, año 2024 - Monar Moreta, Ricardo Ismael (2025)
In the context of public administration, efficiency and quality in service delivery are fundamental factors for improving governmental management. This study proposes the design and implementation of a Quality Management System (QMS) based on the ISO 9001:2015 standard in the Autonomous Decentralized Government (GAD) of the San Miguel canton, with the purpose of optimizing administrative processes and enhancing citizen satisfaction. The general objective of the research is to analyze the impact of a QMS on the efficiency and effectiveness of the GAD’s administrative and service processes, in order to propose strategies for its implementation and sustainability. The methodology used follows a quantitative approach, with a non-experimental, descriptive-applied design. Techniques such as surveys and interviews with GAD officials and citizens were employed, along with a situational analysis of the existing processes. Tools such as the SWOT matrix, PEST analysis, and an evaluation of internal and external factors were applied to identify areas for improvement. The results show that the absence of a QMS has led to operational inefficiencies, deficiencies in process documentation, and limitations in citizen service. The implementation of the ISO 9001:2015 standard would improve internal organization, optimize resources, and strengthen transparency. In conclusion, adopting a QMS is key to improving the quality of public service, reducing response times, and ensuring continuous improvement. It is recommended to train personnel and maintain constant monitoring to ensure the effectiveness of the system.